2022
DOI: 10.1088/1361-6528/ac61ca
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite nanoparticles promote mitochondrial-based pyroptosis via activating calcium homeostasis and redox imbalance in vascular smooth muscle cells

Abstract: Hydroxyapatite nanoparticles (HAP) have been widely used in various fields because of their natural biological origin and functional properties. The emerging evidence on their toxicities has attracted research interest. HAP-induced vascular smooth muscle cell (VSMC) damage is a key step in vascular calcification (VC), particularly in patients with chronic kidney disease. However, the injury effects and mechanism of action of HAP on VSMCs have not been extensively investigated. This study comprehensively charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…These results confirmed the successful construction of the Cur/L-OHP@HAP nanocomposite. A previous report showed that HAP exhibited almost complete dissolution of the deposited layer when immersed in an acidic environment, 28 indicating that HAP can undergo biodegradation at a low pH (such as in the TME) and thereby release calcium and loaded drugs. Therefore, we studied the pH-sensitive, drug-release curves of curcumin, L-OHP, and Ca 2+ in vitro.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…These results confirmed the successful construction of the Cur/L-OHP@HAP nanocomposite. A previous report showed that HAP exhibited almost complete dissolution of the deposited layer when immersed in an acidic environment, 28 indicating that HAP can undergo biodegradation at a low pH (such as in the TME) and thereby release calcium and loaded drugs. Therefore, we studied the pH-sensitive, drug-release curves of curcumin, L-OHP, and Ca 2+ in vitro.…”
Section: Resultsmentioning
confidence: 98%
“…Xia et al discovered that intracellular HAP can undergo biodegradation in an acidic environment and thereby release calcium 28 . To explore this, we used a Fluo‐4 AM probe to detect the production of free Ca 2+ in the cytoplasm of CT26 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Hussain et al reported that multi-walled carbon nanotubes trigger NLRP3 inflammasome activation and consequent cell pyroptosis in primary human bronchial epithelial cells in a concentration- and time-dependent manner ( Hussain et al, 2014 ). Similarly, Xia et al found that hydroxyapatite nanoparticles disrupt Ca 2+ homeostasis in vascular smooth muscle cells; subsequently, they cause mitochondrial dysfunction and cell pyroptosis ( Xia et al, 2022 ). Consistent with previous studies on these NM-induced cellular changes, Du et al’s study revealed how silica nanoparticles initiate mitochondrial ROS production, GSDMD cleavage, and pyroptosis in microglial cells ( Du et al, 2019 ).…”
Section: Definition and Classification Of Pyroptosismentioning
confidence: 99%
“…It was reported that histamine-stimulated IP3R mediates Ca 2+ release from the endoplasmic reticulum to mitochondria, and the increased mitochondrial calcium concentration can enhance oxidative phosphorylation by activating four mitochondrial dehydrogenases, improving the metabolic efficiency of VSMCs, and modulate the phenotypic transition of VSMCs ( 116 ), and PKA/Mfn2 can regulate the connection between mitochondria and ER, the overexpression of Mfn2 can increase the functional coupling between the two organelles, which is conducive to the rapid flow of mitochondrial Ca 2+ ( 116 ). Xia et al found that nanosized hydroxyapatite (nano-HAp) can increase mitochondrial Ca 2+ uptake in VSMCs, which in turn leads to excessive ROS production and oxidation of mtDNA (ox-mtDNA), and the release of more ox-mtDNA from mitochondria to the cytoplasm activates NLRP3/caspase-1/gasdermin D and induce VC by secreting inflammatory factors, antioxidants can effectively reverse this process and alleviate the progress of VC ( 33 ). In addition, the anticoagulants sodium citrate and diethyl citrate can also effectively reduce cell necrosis and lysosomal damage from [Ca2+]i overload induced by nano-HAp, avoiding further VC from cell death ( 29 ).…”
Section: Consequences Of Mitochondrial Dysfunction In Vascular Calcif...mentioning
confidence: 99%